Multidimensional Support Systems in Oncology: Enhancing Quality of Life Through Psychosocial Interventions and Yogic Practice - Singh, Priya Patel (Journal of Educational Research and Policies, 2025)
Cancer remains one of the most psychologically distressing chronic illnesses, often resulting in anxiety, depression, and reduced quality of life. Integrative psychotherapeutic strategies combining social support systems, internal locus of control, and yogic interventions like Yoga Nidra and Preksha Meditation have demonstrated promising outcomes in supporting cancer patients. This article synthesizes the therapeutic dimensions of these approaches using extensive reference to existing literature, including previously published studies on Yoga Nidra, Preksha Meditation, the unconscious mind, and Sattvavajaya Chikitsa, and proposes a multidimensional model to enhance psychological well-being in oncology care.